Impact of digital and electronic technology on suppliers providing outsource manufacturing services for printed documentation and software delivery services in the IT industry. - Toh, Hsing Siong. (2009)
This research seeks to analyze the impact of electronic/digital technology on the companies providing outsource manufacturing and delivery services (documentation and media replication services) in the PC industry. There are three elements affecting the way media replication services and printing facilities are being delivered to the PC manufacturers : (1) competitive pressure among PC manufacturers; (2) a better technological infrastructure; and (3) more technologically literate and sophisticated users. In order to analyze the impacts of technology on such companies, this research would identify the trends and prospects of media replication from the perspective of the customers and the suppliers of such services. The customers are the PC manufacturers such as Compaq and Hewlett Packard, and the software developer such as Microsoft, while the vendors are companies like Stream and Rand McNally.